(untitled) (London Journal of Engineering Research, 2023)
In INDIA population is the root of many problems and is also directly linked with fuel consumption. And with increase in affordability index due to economic growth has led to higher aspiration amongst people (especially a need for increased comfort). With high numbers of vehicle on signals, waiting time increases which leads to a situation of heavy traffic congestion at traffic signals and intersections resulting in a very slow traffic movement even when the traffic lights switch green. An idling vehicle is not only using up valuable fuel and damaging vehicle’s engine, but also causing danger to the environment and a risk to the health of many others. Fuel consumption at signalized intersections has increased, as the vehicles are unable to cross the intersection during one green phase of signal because of long queues at the intersection. Extra fuel loss is due to personal mode of transportation, enhanced trip length and congested intersections. Usually when the vehicles are waiting for their turn to cross the intersection at signals, drivers normally keep their vehicle’s engine on, resulting in extra consumption of fuel. This small amount of fuel wasted, if aggregated over number of cycles per day, for number of days per year and for number of signalized intersections results in a huge quantity of fuel. The wastage of fuel at these intersections results in a huge loss of valuable fuel resources. The paper presents the results of fuel loss at signalized intersections due to delay of vehicle.